2018
DOI: 10.1111/cei.13134
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of membrane-bound and soluble forms of human leucocyte antigen-G in systemic sclerosis

Abstract: Systemic sclerosis (SSc) is a complex disease characterized by immune dysregulation, extensive vascular damage and widespread fibrosis. Human leucocyte antigen-G (HLA-G) is a non-classic class I major histocompatibility complex (MHC) molecule characterized by complex immunomodulating properties. HLA-G is expressed on the membrane of different cell lineages in both physiological and pathological conditions. HLA-G is also detectable in soluble form (sHLA-G) deriving from the shedding of surface isoforms (sHLA-G1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…To our knowledge, only two studies have recently evaluated sHLA-G in sera/plasma samples from patients with SSc ( 52 , 53 ). The first one showed a tendency for lower levels in patients but failed to find statistical difference.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, only two studies have recently evaluated sHLA-G in sera/plasma samples from patients with SSc ( 52 , 53 ). The first one showed a tendency for lower levels in patients but failed to find statistical difference.…”
Section: Discussionmentioning
confidence: 99%
“…Contradictory results could come from the relatively small number of patients [ N = 35 in Ref. ( 53 )] and/or of healthy controls tested in both studies [ N = 32 and 40, respectively ( 52 , 53 )].…”
Section: Discussionmentioning
confidence: 99%
“…Our research group analyzed the role of both membrane HLA-G and sHLA-G in SSc patients. In particular, we recently reported that the percentage of HLA-G-positive monocytes, CD4+ T cells, CD8+ T cells and DP cells are significantly higher in SSc patients as compared to healthy subjects ( 34 ). Among DP cells a subpopulation of CD4 dull CD8 high lymphocytes highly expressing HLA-G was detected.…”
Section: Hla-g-expressing Immune Cells In Autoimmune Diseasesmentioning
confidence: 99%
“…Notably, plasma levels of sHLA-G1 and sHLA-G5 isoforms were comparable and no significant differences were detected in total sHLA-G, sHLA-G1 and sHLA-G5 levels between limited and diffuse SSc forms. The total sHLA-G plasma levels correlated with the elevated TGF-β levels circulating in SSc patients ( 34 ). This finding is in agreement with in vitro data demonstrating that the production of TGF-β by myelomonocytic cells is strongly increased after incubation with recombinant sHLA-G ( 99 ).…”
Section: Hla-g-expressing Immune Cells In Autoimmune Diseasesmentioning
confidence: 99%
See 1 more Smart Citation